Study of Interaction between Unsteady Supersonic Jet and Vortex Rings Discharged from Elliptical Cell. (March 2019) - Ueda, K; Fukuoka, H; Kuniyoshi, N; Yaga, M; Ueno, E; Takiya, T; Fukuda, N
Abstract: The unsteady supersonic jet formed by a shock tube with a small high-pressure chamber was used as a simple alternative model for pulsed laser ablation. Understanding the vortex ring formed by the shock wave is crucial in clarifying behavior of unsteady supersonic jet discharged from elliptical cell. The purpose of this study has been to reveal behavior of the supersonic jet and the vortex rings. The unsteady behavior of a flow is investigated numerically by solving the axisymmetric two-dimensional compressible Navier-Stokes equations. The system of the calculation is a model of laser ablation of a certain duration followed by discharge through the cell exit. The parameters for the calculations are the pressure ratio of the shock tube and the cell diameter. As a result, it was found that the diameter of the elliptical cell had the effect on the interaction between vortex rings and the jet.